2013
DOI: 10.1080/10426914.2012.667893
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mechanical Deformation and Annealing on Kinetics of Martensite in a Stainless Steel

Abstract: An attempt has been made to understand the kinetics concerning the manufacturing schedule of high strength 304 stainless steel comprising formation of strain-induced a 0 martensite in the course of cold rolling (25%) at 0 C and its reversion during annealing in the temperature range of 300-800 C for 1 h. Increase in reversion with increasing annealing temperature without any perceptible grain growth up to 800 C has been demonstrated by the microstructural investigation. X-ray diffraction analysis has revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…From Fig. 3(a), the tensile test results show that the spheroidizing heat treatment leads to an increase in the elongation, and a decrease in the yield and the tensile strengths [1,18]. Based on these experimental results, the stress-strain relationship, with the work-hardening model of the with a diameter of 48.0 mm and height of 100.0 mm.…”
Section: Mechanical Propertiesmentioning
confidence: 90%
“…From Fig. 3(a), the tensile test results show that the spheroidizing heat treatment leads to an increase in the elongation, and a decrease in the yield and the tensile strengths [1,18]. Based on these experimental results, the stress-strain relationship, with the work-hardening model of the with a diameter of 48.0 mm and height of 100.0 mm.…”
Section: Mechanical Propertiesmentioning
confidence: 90%
“…Above a certain temperature, the reverse transformation sets in when martensite transforms back to austenite . The reverse transformation temperature is a function of the extent of deformation and has been reported at temperatures starting from 300 °C . The solubility of hydrogen in martensite is orders of magnitude lower than in austenite and its diffusivity is much higher than austenite .…”
Section: Introductionmentioning
confidence: 96%
“…[1][2][3] Owing to a good combination of excellent ductility, toughness, and corrosion resistance, commercial austenitic stainless steels (ASSs) have been widely used as structural materials for various engineering applications. [4][5][6][7][8][9] However, they exhibit quite low yield strength derived from the coarse γ-austenite (face-centered cubic [FCC]) phase. [9][10][11][12] According to several studies conducted in this research area, the yield strengthening of ASSs can be reached through severe plastic deformation (SPD) methods [6,[11][12][13] via the activation of various strengthening mechanisms, such as grain refining, transformation strengthening, and work hardening.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] Furthermore, it has also been reported that ultrafine grained (UFG) ASSs can be fabricated by conventional rolling and annealing processes. [4][5][6][7]9,[11][12][13][14][15][16][17] The principle is to use cold rolling (CR) to produce DIM and the subsequent annealing to revert the DIM back to nano-or ultrafinegrained austenite under specific conditions. [4][5][6]9,[12][13][14][15]17] Additionally, the ultrafine or fine-grained strengthening is a hopeful pathway to improve simultaneously the yield strength, toughness, and corrosion resistance of ASSs without obviously deteriorating ductility and work-hardening ability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation